Leverage, liquidity, and working capital efficiency affect manufacturing companies' profitability on the IDX - Anandes Langguana (Enrichment : Journal of Management, 2023)
Anuraga, W., & Sitohang, S. (2019). Pengaruh Produk, Harga, Promosi, dan Merk terhdap Keputusan 9). Dimensions and Types of Supervisory Control: Effects on Salesperson Performance and Satisfaction. Journal of Marketing, 60(1), 89–. Arianti , A. (2019). Pengembangan Variasi Mengajar dalam Meningkatkan Motivasi Belajar. Jurnal Manajemen Pendidikan, 696-714 Arifuddin, R. R., Kadir, A. R., & Kadir, N. (2019). Pengaruh Personal Selling dan Digital Marketing terhadap Keputusan Pembelian Polis Asuransi PT. GBE General Insurance Indonesia Cabang Makassar. Hasanuddin Journal of Applied Business and Entrepreneurship, 2(3), 92–10 Azzahrani, M. (2019). Strategi Komunikasi Pemasaran Kementerian Pariwisata Indonesia dalam Pesona Indonesia melalui Youtube. 2(2), 144–161. Bali, A.O. (2023). Public engagement in government officials’ posts on social media during coronavirus lockdown. PLoS ONE. Baran, Stanley, J & Davis, D.K. (2019). Mass Communication Theory: Foundations Ferment, and Future. Seventh Edition. Cengage Learning. Chandra, E. (2019). Youtube, Citra Media Informasi Interaktif Youtube, Citra Media Informasi Interaktif atau Media Penyampaian Aspirasi Pribadi. www.YouTubenocookie.com. Creswell, J. W. (2019). Research Design Qualitative, Quantitative, and Mixed Methods Approaches 4th Edition. Eribka, et al. (2019). Pengaruh Konten Vlog dalam Youtube terhadap Pembentukan Sikap Mahasiswa Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Sam Ratulangi. In Acta Diurna: Vol. VI (Issue 1). Ezza, Debra Muttaqin. (2021). Dampak Media Social Youtube terhadap Perkembangan Ahlak Remaja di Kelurahan Gunung Agung Kecamatan Langkapura RT: 006 RW: 00. Faiqah, F., Nadjib, M., & Amir, A. S. (2019). Youtube sebagai Sarana Komunikasi bagi Komunitas Makassarvidgram. In Jurnal Komunikasi KAREBA (Vol. 5, Issue 2). Fors, A. (2019). The Power of social media when creating business networks-The Future Valley in Borlänge. Gumilar, G. (2015). Pemanfaatan Instagram sebagai Sarana Promosi oleh Pengelola Industri Kreatif Fashion di Kota Bandung. Graham, Missy. Et. al. (2019). Government Public Relations and Social Media: An Analysis of the Perceptions and Trends of Social Media Use at the Local Government Level. Public Relations Journal Vol. 7, No. 4 Griffin, et al. (2019). A First Look at Communication Theory, Tenth Edition. McGrawHill Education. Idris, I.K. (2019). Government Social Media in Indonesia: Just Another Information Dissemination Tool. Jurnal Komunikasi Malaysian Journal of Communication Jilid 34(4) Idris. I.K. (2019). Peran Humas Pemerintah di Era Keterbukaan Informasi (Analisis Isi Permenpan-RB No.6 Tahun 2014 tentang Jabatan Fungsional Pranata Humas dan Angka Kreditnya).. Jurnal Universitas Paramadina Vol. 11 No. 3 Desember 2014. Irwanto, et.al. (2022). The Role of Public Relations in Disseminating Government Programs Through Social Media. East Asian Journal of Multidisciplinary Research (EAJMR) Vol. 1, No. 5. Jones, Ron. “Social Media Marketing 101, Part 1.” Search Engine Watch. 29 Februari 2019. http://sbinfocanada.about.com/gi/o.htm?zi=1/XJ&zTi=1&sdn=sbinfocanada&cdn=money&tm=22&f=00&tt=8&bt=9&bts=83&zu=http%3A//searchenginewatch.c om/3632809 (accessed September 23, 2019) Kotler, P., Kartajaya, H., & Setiawan, I. (2021). From Products to Customers to the Human Spirit: Marketing 3.0. Hoboken. John Wiley & Sons. Khaerati, R. (2021). Strategi Komunikasi Pemerintah Daerah dalam Penanganan Covid19 di Kabupaten Gowa. Kuitunen, M. (2019). Building a Successful Personal Brand on YouTube. Lee, Mordecai, et.al. (2022). The Practice of Government Public Relations, Second Editions. American Society for Public Administration Labas, Y. N., & Yasmine, D. I. (2017). Komodifikasi di Era Masyarakat Jejaring Studi Kasus YouTube Indonesia. Jurnal Pemikiran Sosiologi, 4. Maulana, F. (2021). Pengaruh Daya Tarik Iklan dan Brand Image melalui Akun Instagram @Tangsel.Life terhadap Brand Awareness Camelia Resto serta Dampaknya pada Keputusan Pembelian. Merriam-Webster. “Social Media.” Merriam-Webster. 2019.http://www.merriamwebster.com/dictionary/social%20media (accessed September 23, 2019) Meutia, et al. (2019). Fenomena Penggunaan Media Sosial Instagram sebagai Komunikasi Pembelajaran Agama Islam oleh Mahasiswa FISIP Universitas Riau. In JOM FISIP (Vol. 4, Issue 2). Mogallapu, A. (2019). Social network analysis of the video bloggers’ community in YouTube. https://scholarsmine.mst.edu/masters_theses/4879 Motion, Judy, Heath, Robert L, Leitch, & Shirley. (2016). Social Media and Public Relations. Nugeraha, A. et al. (2020). Analisis Fungsi Instagram sebagai Media Penyebar Informasi Kriminal di Kota Samarinda. EJournal Lmu Komunikasi, 2020, 1 (1): 1-15. Nursidah. (2021). Strategi Penggunaan Youtube Sebagai Sarana Menyebarluaskan Berita (Studi Terhadap Kompas TV Jambi). Pongtiku, Arry, (2018) Metode Penelitin Kualitatif Saja. Nulisbuku.com Pratten, Robert. (2019). Getting Started in Transmedia Storytelling: A Practical Guide for Beginner, Second Edition. Rachmawati, F. (2022). Peran Agenda Building Bagi Public Relations. Jurnal Jispendiora, Vol 1. Rogeleonick, A. (2019). Analisis Pengaruh Unggahan Instagram terhadap Niat Publik untuk Terlibat dalam Kebijakan Pendidikan: Studi Kasus Kementerian Pendidikan dan Kebudayaan. Universitas Indonesia. Sari, D. N., & Basit, A. (2020). Media Sosial Instagram Sebagai Media Informasi Edukasi Parenting. PERSEPSI: Communication Journal, Vol 3No. 1, 2020, 3(31), 23–36. Smith, A., Fischer, E., & Chen, Y. (2020). How does brand-related user-generated content differ across YouTube, Facebook, and Twitter? Journal of Interactive Marketing. Sofkathin, S. (2021). Komunikasi Persuasif dalam Konten Youtube Analisa Channel: Self Love Day 1-7 (Analisis Hermeneutika Gadamer). Sriwahyuni, W. (2019). Analisis Pemanfaatan Media Sosial dalam Menunjang Proses Pembelajaran Siswa SMUN 1 Makassar. Stellarosa, Y., Firyal, S. J., & Ikhsano, A. (2019). Pemanfaatan Youtube sebagai Sarana Transformasi Majalah Highend. 2(2), 59. http://ojs.stiami.ac.id. Itqiya, F. (2019). Pengaruh Motif Penggunaan Media terhadap Kepuasan Pengguna Video dan Foto di Instagram AA Gym. Yin, R. K. (2019). Case Study Research and Applications. Sixth Edition Yossita, Wisman. 2020. Sistem Komunikasi Pendidikan. Yogyakarta : Universitas Negeri Yogyakarya Press. Yuenda Pramata Dewi, Y. A. (2021). Penggunaan Twitter terhadap Pembelajaran Bahasa Indonesia. Seminar Internasional Riksa Bahasa (pp. 307-312). Bandung: proceedings.upi.edu.